Odpowiedzi

2009-11-08T20:44:25+01:00
A) x(x²+3x+3)+9
b)x(x-y-2)+2y
c) m(m+n-5)-5n
d)a(a-b-3)+3b
e)a(10y+2x)-b(5y+x)
f)3b(2y-5x)+2a(2y+5x)
g)5(a²-ax)-7(a-x)
h)4x(x-z)-3(x-z)
Najlepsza Odpowiedź!
2009-11-08T20:49:50+01:00
A) x³+3x²+3x+9= x²(x+3)+3(x+3)=(x²+3)(x+3)
b)x²-xy-2x+2y=x(x-y)-2(x-y)
c)m²+mn-5m-5n=m(m+n)-5(m+n)
d)a²-ab-3a+3b=a(a-b)-3(a-b)
e)10ay-5by+2ax-bx=5y(2a-b)+x(2a-b)=(5y+x)(2a-b)
f)6by-15bx-4ay+10ax=3b(2y-5x)-2a(2y-5x)=(3b-2a)(2y-5x)
g)5a²-5ax-7a+7x=5a(a-x)-7(a-x)=(5a-7)(a-x)
h)4x²-4xz-3x+3z=4x(x-z)-3(x-z)=(4x-3)(x-z)
1 5 1